Precise tip positioning of a flexible manipulator using resonant control - Mahmood, Iskandar Al-Thani; Moheimani, S. O. Reza; Bhikkaji, Bharath (2007)
A single-link flexible manipulator is fabricated to represent a typical flexible robotic arm. This flexible manipulator is modeled as a SIMO system with the motor-torque as the input and the hub angle and the tip position as the outputs. The two transfer functions are identified using a frequency-domain system identification method. A feedback loop around the hub angle response with a resonant controller is designed to damp the resonant modes. A high gain integral controller is also designed to achieve zero steady-state error in the tip position response. Experiments are performed to demonstrate the effectiveness of the proposed control scheme.